Without regard to race : the other Martin Robison Delany - Adeleke, Tunde (University Press of Mississippi, 2003)
Before Marcus Garvey and W.E.B. Du Bois lifted the banner for black liberation and independence, Martin Robison Delany (1812-1885) was at the forefront. He was the first black appointed as a combat major in the Union army during the Civil War. He was a pan-Africanist and a crusader for black freedom and equality in the nineteenth century. For the past three decades, however, this precursor has been regarded only as a militant black nationalist and "racial essentialist." To his discredit, his ideas, programs, and accomplishments have been maintained as models of uncompromising militancy. Clas